Mad Hatter's tea party flyer - Unidentified author (Colorado State University. Libraries, 1993)
Advertisement flyer for Mad Hatter's Tea Party, a fundraiser for Gustafson Gallery held at Ammons Hall.
Keywords: Fashion -- History; Fashion -- Exhibitions